Voor alles pastor : de zorg van Joseph Doucé voor sexuele minderheden. - van Kilsdank, Jan; Bruin, Gerard; Schenkel, Simone (Aalsmeer : DABAR Luyten, 1993)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie